2000
DOI: 10.1021/jm000117y
|View full text |Cite
|
Sign up to set email alerts
|

3-(Hydroxymethyl)-Bearing Phosphatidylinositol Ether Lipid Analogues and Carbonate Surrogates Block PI3-K, Akt, and Cancer Cell Growth

Abstract: Phosphatidylinositol 3-kinase (PI3-K) phosphorylates the 3-position of phosphatidylinositol to give rise to three signaling phospholipids. Binding of the pleckstrin homology (PH) domain of Akt to membrane PI(3)P's causes the translocation of Akt to the plasma membrane bringing it into contact with membrane-bound Akt kinase (PDK1 and 2), which phosphorylates and activates Akt. Akt inhibits apoptosis by phosphorylating Bad, thus promoting its binding to and blockade of the activity of the cell survival factor Bc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
144
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(147 citation statements)
references
References 24 publications
3
144
0
Order By: Relevance
“…This inhibitor did not interfere with phosphorylation of Akt itself (Figure 5d). The concentration of Akt inhibitor used (10 mM) was two-fold above its IC 50 for suppression of Akt and eightfold below its IC 50 for PI3K, 45 suggesting that this response was relatively Akt specific. pp60 c-src activity may also play a role in this part of the pathway, since it is required for signaling from PI3K to S6K and from RANKL to Akt.…”
Section: Ocl Require Continuous Protein Translation For Survivalmentioning
confidence: 99%
“…This inhibitor did not interfere with phosphorylation of Akt itself (Figure 5d). The concentration of Akt inhibitor used (10 mM) was two-fold above its IC 50 for suppression of Akt and eightfold below its IC 50 for PI3K, 45 suggesting that this response was relatively Akt specific. pp60 c-src activity may also play a role in this part of the pathway, since it is required for signaling from PI3K to S6K and from RANKL to Akt.…”
Section: Ocl Require Continuous Protein Translation For Survivalmentioning
confidence: 99%
“…These results suggest that PI-3K and molecules downstream of it are involved in the IL-4-mediated protection. To test whether Akt function is directly involved with the IL-4-mediated protection from apoptosis, we cultured CH31 cells in the presence of the Akt inhibitor AktI, which prevents binding of Akt to D3 phosphatidylinositol (PIP3) [53]. We observed that this inhibitor also abrogated the ability of IL-4 to protect cells from anti-IgM-induced apoptosis ( Figure 7C), suggesting that Akt activity and its downstream sequelae contribute to the anti-apoptotic activity of IL-4 in this model.…”
Section: Effects Of Il-4 Signaling On the Pi-3k/akt Pathway And Protementioning
confidence: 99%
“…21,22 Recently, a selective Akt pharmacological inhibitor, 1L-6-hydroxymethyl-chiro-inositol 2(R)-2-O-methyl-3-O-octadecylcarbonate (Akt inhibitor), has been synthesized. 23 HL60 cells derived from a human acute promyelocytic leukemia and are usually sensitive to chemotherapeutic drugs and TRAIL. We have described an HL60 leukemia human cell clone (named HL60AR) with a constitutively activated PI3K/Akt axis.…”
Section: Introductionmentioning
confidence: 99%